2021
DOI: 10.3390/agronomy11122476
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Cordyceps javanica (Hypocreales: Cordycipitaceae) to Diaphorina citri (Hemiptera: Liviidae) Adults, with Ultrastructural Observations on the Fungal Infection Process

Abstract: Entomopathogenic fungi are proposed biological control agents against the Asian citrus psyllid (Diaphorina citri). We quantified the pathogenicity of Cordyceps javanica strain Apopka 97 strain (Cja Apopka 97) (blastospores and conidia) against D. citri using the spray technique. We also used light and scanning electron microscopy to observe the Cja Apopka 97, infection process against D. citri adults at different stages pre- and post-mortem. Our findings demonstrated that psyllid mortality in the blastospore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The C. javanica fungus had its efficiency evaluated in five studies. Hussain et al (2021), using scanning electron microscopy, found that the stages of the C. javanica infection process include spore adherence and germ tube formation within 24 hours after inoculation, penetration pins and mycelium growth on the wings of psyllids after 72 hours, cuticle rupture after 96 hours, and mycelial mass colonizing the host's body after 144 hours. Under laboratory conditions, carrying out treatment with blastospores, the mortality rate reached 100% within seven days after exposure to a concentration of 1x10 7 spores/mL.…”
Section: Rosasmentioning
confidence: 99%
“…The C. javanica fungus had its efficiency evaluated in five studies. Hussain et al (2021), using scanning electron microscopy, found that the stages of the C. javanica infection process include spore adherence and germ tube formation within 24 hours after inoculation, penetration pins and mycelium growth on the wings of psyllids after 72 hours, cuticle rupture after 96 hours, and mycelial mass colonizing the host's body after 144 hours. Under laboratory conditions, carrying out treatment with blastospores, the mortality rate reached 100% within seven days after exposure to a concentration of 1x10 7 spores/mL.…”
Section: Rosasmentioning
confidence: 99%